Comparison of Aerobic Strengthening Exercise Vs Conventional Exercise in Reducing Pain and Improving Balance in Osteoarthritis Knee Subject. - Joy, Judith; Kotteeswaran, K. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Osteoarthritis is a chronic knee disease that is caused due to wear and tear injury or inflammation in the joint causing pain and limiting ROM. The condition leads to joint stiffness which causes joint weakness and loss of stability and balance. The purpose of this study is to determine whether ASE or CE is effective in reducing pain and improving balance in an OA knee subject. Purpose: To find out the effect of aerobic strengthening exercise and conventional exercise in reducing pain and improving balance in osteoarthritis knee. Materials and Methods: 198 individuals aged from 55 to 70 of both genders suffering from pain and reduced balance in OA knee participated in the study taken from Dynamics physiotherapy and rehabilitation centre. The individuals were randomly assigned into two groups. Group A received ASE; Group B received CE for 4 weeks. The functional state of the subjects was evaluated pre and post using the NPRS and TUG test. The entire process was conducted from November 2022 to March 2023. Results: Aerobic strengthening exercise was found to be effective compared to conventional exercise in improving balance and reducing pain in OA knee subjects. Conclusion: Group A had better balance and seemed to have reduced pain in OA knee during ADL compared to Group B. It is concluded that ASE provides balance and reduces pain and is seen as an effective treatment in OA knee.